Screening of the kernels of Pentadesma butyracea from various growing sites of Benin and evaluation of their antioxidant pigments content - AYEGNON, Bernolde Paul; KAODE, A. PIERRE POLYCARPE; GNANVI, GLAWDYS; MADODE, Yann; FAGLA-AMOUSSOU, Balbine; AZOKPOTA, PAULIN; SOUMANOU, Mohamed; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2015)
Pentadesma butyracea Sabine (Clusiaceae) is a ligneous forest species of multipurpose uses. It is widely distributed in Africa from Guinea-Bissau to the West of the Democratic Republic of Congo. This study screened the kernel of P. butyracea on the basis of their physico-chemical properties. Six types of kernels were distinguished. The plant producing type 1 kernels (with medium length, low width and high thickness) and type 5 kernels (with high length, high width and high thickness) predominate within accessions representing 63% of the collections. Significant differences were found in the structural composition of the kernels. The average level of oil concentration in the kernels was 46.77%. The 1000 kernel weight averaged to 6.46 kg. The kernel hardness averaged to 550.81 N and is similar for all accessions but revealed that P. butyracea kernel is harder than shea kernel. The total phenolics and the total anthocyanins contents of the kernels varied significantly among accessions with a mean value of 164.03 and 152.78 mg/100 g, respectively. The antioxidant activity in the extract from P. butyracea kernel ranged from 30.22 to 58.57% of the remaining 2,2-diphenyl-1-picrylhydrazyl (DPPH) and is comparable to many traditional sources of antioxidants.
Keywords: Pentadesma butyracea; kernel; butter; antioxidant; cosmetic